Antihelminthic Activity of Lophira Lanceolata on Heligmosomoides polygyrus Using an Automated High-Throughput Method - Yamssi Cédric; Noumedem Anangmo Christelle Nadia; Simeni Njonnou Sylvain Raoul; Samuel Berinyuy; Mounvera Abdel Azizi; Tientcheu Noutong Jemimah Sandra; Ngouyamsa Nsapkain Aboubakar Sidiki; Vincent Khan Payne (Journal of Tropical Medicine)
Background. There are about 13 parasitic infections that are responsible for significant morbidity and mortality but have not received the attention they deserve; thus, they are now known as “neglected tropical diseases” (NTDs). This study was aimed at evaluating the antihelminthic activities of Lophira lanceolata using an automated high-throughput method. Methods. The antihelminthic activity effect of the extracts against H. polygyrus was determined using an automated high-throughput method. For the egg-hatching test, 100 μL of embryonated egg suspension (60 eggs) was added to 100 μL of various concentrations of extracts, levamisole, and 1.5% DMSO in a 96-well round-bottom microtitre plate. After mixing, the 96-well microplate was placed in WMicroTracker and incubated for 24 h at 25°C; the movements were recorded every 30 minutes. The same procedure was used for the larval motility assays, where 100 μL of L1 or L2 larvae (50 larvae) were put in contact with 100 μL of various concentrations of extracts. Results. The ovicidal activity (hatching) had an IC50 of 1.4 mg/mL for the ethanol extract. The aqueous and ethanol extracts of L. lanceolata showed larvicidal activity on the L1 larvae with IC50 of 1.85 mg/mL and 2.4 mg/mL, respectively, as well as on the L2 larvae with IC50 values of 1.08 mg/mL and 1.02 mg/mL for the aqueous and ethanol extracts, respectively. These results showed that the aqueous extract exhibited a stronger inhibitory power on the hatching rate of parasites than ethanol extracts, while the contrary effect was observed for the larval motility assays. Conclusion. This study provides scientific data on the use of L. lanceolata by the local population for the treatment of helminthiases. However, in vivo and toxicity tests are necessary to assess its activity and safety.